Cause of Death Among Patients With Peripheral Artery Disease: Insights From the EUCLID Trial. Issue 11 (November 2020) - Kochar, Ajar; Mulder, Hillary; Rockhold, Frank W.; Baumgartner, Iris; Berger, Jeffrey S.; Blomster, Juuso I.; Fowkes, F. Gerry R.; Katona, Brian G.; Lopes, Renato D.; Al-Khalidi, Hussein R.; Mahaffey, Kenneth W.; Norgren, Lars; et al.
Abstract : Background: Peripheral artery disease is common and associated with high mortality. There are limited data detailing causes of death among patients with peripheral artery disease. Methods: EUCLID (Examining Use of Ticagrelor in Peripheral Artery Disease) was a randomized clinical trial that assigned patients with peripheral artery disease to clopidogrel or ticagrelor. We describe the causes of death in EUCLID using mortality end points adjudicated through a clinical events classification process. The association between baseline factors and cardiovascular death was evaluated by Cox proportional hazards modeling. The competing risk of noncardiovascular death was assessed by the cumulative incidence function for cardiovascular death and the Fine and Gray method to ascertain the association between baseline characteristics and cardiovascular mortality. Results: A total of 1263 out of 13 885 (9.1%) patients died (median follow-up: 30 months). There were 706 patients (55.9%) with a cardiovascular cause of death and 522 (41.3%) with a noncardiovascular cause of death. The most common cause of cardiovascular death was sudden cardiac death (20.1%); while myocardial infarction (5.2%) and ischemic stroke (3.2%) were uncommon. The most common causes of noncardiovascular death were malignancies (17.9%) and infections (11.9%). The factor most associated with a higher risk of cardiovascular death was age per 5 year increase (HR, 1.26 [95% CI, 1.20–1.32]). Female sex was associated with a lower risk of cardiovascular death (HR, 0.68 [95% CI, 0.56–0.82]). To evaluate the effect of noncardiovascular death as a competing risk, we superimposed the cumulative incidence function curve with the Kaplan-Meier curve. These curves closely approximated each other. After accounting for the competing risk of noncardiovascular death, the magnitude and direction of the factors associated with cardiovascular death were minimally changed. Conclusions: Among patients with symptomatic peripheral artery disease, noncardiovascular causes of death reflected a high proportion (40%) of deaths. Accounting for noncardiovascular deaths as a competing risk, there was not a significant change in the risk estimation for cardiovascular death. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT01732822. Abstract : Supplemental Digital Content is available in the text.